THE POTENTIAL OF GAME TECHNOLOGIES IN CORRECTING PRIMARY SCHOOL STUDENTS' SPEECH IN NATIVE LANGUAGE LESSONS - Xolmurodova Yorqinoy Zokir qizi (International Journal of Literature and Language Studies, 2026)
This article highlights the significance of game technologies in addressing and correcting specific speech deficiencies among primary school students in native language classes. The paper analyzes the methodological potential of didactic games in speech correction, fixing phonetic and grammatical errors, enriching vocabulary, and developing free-speaking skills. Furthermore, it provides practical recommendations for the effective organization of speech-oriented games in primary native language lessons, which aim to enhance students' engagement while simultaneously helping them overcome barriers in their speech development.